Iris image segmentation based on approximate methods with subsequent refinements - Gankin, K. A.; Gneushev, A. N.; Matveev, I. A. (Journal of computer & systems sciences international, 2014)
A system of methods for the detection and segmentation of iris in frontal eye images is presented. Input data are images used in modern iris recognition systems. Coordinates of outer and inner iris borders and the mask of the visible iris region or a decision that the image does not contain the iris of acceptable quality are obtained at the output. The system starts processing with an approximate detection of the eye center followed by an approximate detection of the outer and inner iris borders. If one of these borders is not detected, a further attempt is made to locate it using a different algorithm. Ultimately, the precise borders of the iris are determined at the last steps using specifically designed methods. The system is tested on public iris image databases as well as using the international IREX NIST test.